Preclinical Reproductive and Developmental Toxicity Profile of a Glycine Transporter Type 1 (Glyt1) Inhibitor. Issue 3 (24th May 2016) - Barrow, Paul; Parrott, Neil; Alberati, Daniela; Paehler, Axel; Koerner, Annette
Abstract : Bitopertin is a glycine type 1 (GlyT1) inhibitor intended for the treatment of psychiatric disorders. The principle adverse effect in the regulatory reproductive toxicity studies was peri‐natal pup death when rat dams were treated during parturition at a dose resulting in five‐times the human therapeutic exposure (AUC). Cessation of dosing two days before parturition prevented the pup deaths. Investigatory experiments and pharmacokinetic modelling suggested that the neonatal mortality was related to transplacental passage of bitopertin leading to high systemic levels in the newborn pups. Brain levels of bitopertin in the rat fetus and neonate were two‐fold higher than in the mother. As illustrated by knock‐out mice models, GlyT1 function is essential for neonatal pup survival in rodents, but is not necessary for normal prenatal morphological development. The glycine transport systems are immature at birth in the rat, but are functionally well‐developed in the human newborn. While the relevance to humans of the neonatal mortality seen in rats following late gestational exposure is unknown, bitopertin would not be recommended for use during late pregnancy unless the anticipated benefit for the mother outweighs the potential risk to the newborn.